DHA intake interacts with ELOVL2 and ELOVL5 genetic variants to influence polyunsaturated fatty acids in human milk - Wu霞吴义, Yixia; Wang 烟王, Yan; Tian敏田慧, Huimin; Lu逯通, Tong; Yu苗于, Miao; Xu慧徐文, Wenhui; Liu良刘国, Guoliang; Xie林谢, Lin (Journal of lipid research, 2019)
Endogenous synthesis of PUFAs is mediated by genes controlling fatty acid elongases 2 and 5 (ELOVL2 and ELOVL5) and by exogenous DHA intake. Associations between elongases and PUFA levels probably involve genetic variants of ELOVL and changes in DHA intake, but data about their combined effect on PUFA levels are sparse. We hypothesized that each factor would directly affect PUFAs and that interactions between haplotypes and DHA intake would influence PUFAs. We explored four levels of DHA intake in pregnant Chinese Han women and 10 SNPs in the ELOVL genes to determine associations with PUFAs in breast milk. The SNP rs3798713 and 3-SNP haplotype (rs2281591, rs12332786, and rs3798713) in ELOVL2 were associated with linoleic acid (LA) concentrations. However, carriers of the 3-SNP haplotype with higher DHA intake (second quartile: 14.58–43.15 mg/day) had higher concentrations of LA, arachidonic acid, EPA, and DHA compared with the interaction baseline. In ELOVL5, five SNPs (rs2294867, rs9357760, rs2397142, rs209512, and rs12207094) correlated with PUFA changes. Compared with those who had the 5-SNP haplotype C-A-C-G-A and low DHA intake (<14.58 mg/day), carriers with other haplotypes (A-A-C-A-A or C-A-C-A-A) and high DHA intake (≥118.82 mg/day) had increased EPA levels after adjustments for age and BMI. This study showed that maternal genetic variants in ELOVL2 and ELOVL5 were associated with PUFA levels in breast milk and that the combination of SNP haplotypes and higher DHA intake increased PUFA concentrations.